The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/jcm.00637-16
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of a Point-of-Care Downward-Flow Assay for Simultaneous Detection of Antibodies to Treponema pallidum and Human Immunodeficiency Virus

Abstract: dCombining the detection of syphilis and HIV antibodies into one point-of-care test integrates syphilis screening into already existing HIV screening programs, which may be particularly beneficial in settings such as antenatal care. Using the INSTI Multiplex downward-flow immunoassay, we tested 200 stored serum samples from high-risk patients enrolled in a longitudinal study on HIV infection and syphilis in Peruvian men who have sex with men and transgender women. This rapid assay detected HIV and Treponema pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This makes the sensitivity and specificity calculations very comparable between the four assays. Sensitivities and specificities obtained for anti-HIV antibody detection (Table 2) are in line with results from earlier published laboratory evaluations for all four assays [37, 9, 1114, 1621]. For Treponema pallidum , however, the sensitivities obtained in our study were lower compared to earlier published data for all assays, while specificities were comparable.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This makes the sensitivity and specificity calculations very comparable between the four assays. Sensitivities and specificities obtained for anti-HIV antibody detection (Table 2) are in line with results from earlier published laboratory evaluations for all four assays [37, 9, 1114, 1621]. For Treponema pallidum , however, the sensitivities obtained in our study were lower compared to earlier published data for all assays, while specificities were comparable.…”
Section: Discussionsupporting
confidence: 91%
“…SD Bioline previous laboratory evaluations: references [5, 7, 1214, 16, 17, 20, 21, 23, 24]; SD Bioline previous field evaluations: references [8, 11, 15]; DPP previous laboratory evaluations: references [5, 17–19, 23]; Multiplo previous laboratory evaluations: references [5, 6, 17, 23]; Multiplo previous field evaluations: reference [10]; Insti previous laboratory evaluation: reference [9] NA Not available a range from lowest obtained sensitivity or specificity to highest…”
Section: Discussionmentioning
confidence: 99%
“…One study was identified that evaluated the diagnostic accuracy of the INSTI Multiplex downward-flow immunoassay 48 (also called the INSTI Multiplex HIV-1/HIV-2/Syphilis Antibody Test) (bioLytical Laboratories, Canada). Using 200 archived serum specimens from high-risk individuals in Peru, the results of this study suggested a high sensitivity (100%, 95% CI 95.9% to 100%) and specificity (95.5%, 95% CI 89.9% to 98.5%) for HIV diagnosis and a slightly lower sensitivity (87.4%, 95% CI 81.4% to 92.0%) but a higher specificity (97%, 95% CI 84.2% to 99.9%) for syphilis diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Multiplex point-of-care immunoassays for HIV and syphilis as well as mosquito-borne diseases have been tested, and are commercially available for HIV and syphilis. [66][67][68][69] Using bacteriophage display libraries, epitopes for thousands of viral strains have been generated to detect exposure to almost every virus. 58 Diagnosis of neglected tropical diseases such as human African trypanosomiasis and visceral leishmaniasis has traditionally required complex or unreliable serologic methods, but lateral flow tests to replace them have now been developed and commercialized.…”
Section: Traditional Microbiology Techniques Reinvent Themselvesmentioning
confidence: 99%